PERLINDUNGAN HUKUM TERHADAP KREDITUR ATAS GUGATAN DEBITUR MENGENAI EKSEKUSI HAK TANGGUNGAN - Anindita, Faizah (Ensiklopedia of Journal, 2025)
Abstract: This study intends to analyse the legal safeguards available to creditors against litigation for the enforcement of mortgage rights, specifically through the examination of Supreme Court Decision Number 376/PDT/2019/PT BDG.  This study employs a normative legal research methodology utilising a statutory approach, a conceptual approach, and a case law approach.  Secondary data is subjected to qualitative analysis.  Formulating conclusions through deductive reasoning.  The analysis results indicate that the auction for the execution of mortgage rights conducted in compliance with legislative provisions cannot be lawfully annulled.  The judge asserted in his ruling that the debtor's claim was unfounded due to the existence of a default.  Consequently, legislative safeguards for creditors, encompassing both preventive and punitive measures, are crucial for ensuring legal certainty in the provision of collateralised credit. Keywords: Legal Protection, Auction, Judge's Consideration.